(untitled) (Pravaha, 2020)
The purpose of this study is to examine the impact of the glass ceiling (GC) on women’s career development (WCD)in Nepalese commercial banks. One hundred and forty-four women branch managers working in different branches were taken as the sample. The study used a survey questionnaire (17 items) derived from women workplace culture questionnaire (WWC) (Bergman and Hallberg,2002) for measuring glass ceiling, used as an independent variable in the study. Additionally, a career satisfaction questionnaire developed by (Greenhaus, Parasuraman, and Wormley1990) was used to measure WCD (dependent variable).The statistical tools like Pearson correlation and regression analysis were applied to find the result of quantitative data. The result revealed that there is an existence of GC in commercial banks in Nepal and the negative relationship between GC and the WCD along with the impact of the corporate climate on the WCD. Some limitations of the study have been found and implications and recommendation for the future researchers are also discussed.